2013
DOI: 10.4103/2277-9175.108001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aqueous cinnamon extract on the apoptotic process in acute myeloid leukemia HL-60 cells

Abstract: Background:Acute promyelocytic leukemia (APL) is an acute leukemia diagnosed by translocation of chromosomes 15 and 17 [T (15,17)] and aggregation of neoplastic promyelocytes which are incapable of being converted into mature cells. Today, many tend to use medicinal herbs in studies and clinical applications for treatment of cancers. Cinnamon with scientific name “cinnamomumzelanicum” is a shrub of Laurales order, lauraceae family with cinnamomum genus. It is a medicinal shrub with anti-proliferation effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Scientists treated mouse melanoma cells with cinnamon extract at various doses (0.3 or 0.5 mg/mL) and then evaluated the levels of pro-angiogenic molecules; RT-PCR and ELISA methods were used to detect the expression of VEGF, PDGF and TGF-b, and it was demonstrated that aqueous cinnamon extract inhibited these factors both in mRNA and in proteins ( Figure 2 ). Its activity is clinically evident, too, if we pay attention to the dimensions of the spleen and lymph nodes, which are significantly smaller in mice treated with this extract than those in untreated mice [ 56 ]. HIF-1a is a transcription factor whose activity depends on tissue oxygen levels, [ 8 , 18 ].…”
Section: Cinnamon and Cancer: Pathways And Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists treated mouse melanoma cells with cinnamon extract at various doses (0.3 or 0.5 mg/mL) and then evaluated the levels of pro-angiogenic molecules; RT-PCR and ELISA methods were used to detect the expression of VEGF, PDGF and TGF-b, and it was demonstrated that aqueous cinnamon extract inhibited these factors both in mRNA and in proteins ( Figure 2 ). Its activity is clinically evident, too, if we pay attention to the dimensions of the spleen and lymph nodes, which are significantly smaller in mice treated with this extract than those in untreated mice [ 56 ]. HIF-1a is a transcription factor whose activity depends on tissue oxygen levels, [ 8 , 18 ].…”
Section: Cinnamon and Cancer: Pathways And Mechanisms Of Actionmentioning
confidence: 99%
“…The administration of cinnamon extract down-regulates levels of HIF1a, conducting a reduction in the formation of new blood vessels. This evidence allows us to state that cinnamon inhibits neo-angiogenesis [ 56 ].…”
Section: Cinnamon and Cancer: Pathways And Mechanisms Of Actionmentioning
confidence: 99%
“…Moulavi et al, plant extracts was observed in the normal cell viability assays (Assadollahi et al, 2013;Shokrzadeh et al, 2009). Studies suggest that people who eat more vegetables and fruits, which are rich sources of antioxidants such as vitamin C, vitamin E, carotenoids and many other phytochemicals, may have a lower risk for some types of cancer (Hocman, 1989).…”
Section: Effects Of Rhamnus Frangula Miller Leaf and Bark Extracts On...mentioning
confidence: 99%
“…In addition to being an antioxidant [4], antifungal [5], and antibiotic agent [4], it is effective in treating diseases, such as obesity [6], Parkinson's [7], cancer, and cardiovascular disease [8]. The effectiveness of this substance on various cancer cells such as leukemia [9], prostate [10], and breast cancer [11] was evaluated.…”
Section: Introductionmentioning
confidence: 99%